The Evaluation Of Islamic Da’Wah In Bangladesh Between Past and Present: An Analytical Comparative Study (Contrarius Series: Law & Social Justice, 2026)
Islamic Da‘wah in Bangladesh has been one of the central pillars in shaping the religious and cultural identity of the Bengali people since the arrival of Islam in the region during the medieval period. The early contributions of Sufi Du‘āt (preachers), scholars, and traders played a decisive role in establishing the principles of Islamic faith and in building strong social and cultural bonds. As a result, Da‘wah became a key factor in constructing the national and religious character of the Bangladeshi people. Over the course of history, however, Da‘wah in Bangladesh experienced diverse transformations linked to political conditions—such as British colonialism and the subsequent movements for liberation and independence—social dynamics, including popular mobilizations and the proliferation of religious educational institutions, as well as intellectual and technological developments in the modern era. This study seeks to conduct a comparative analytical investigation into the evolution of Islamic Da‘wah in Bangladesh between past and present. It focuses on tracing the methods and approaches employed by Du‘āt across different historical periods, analyzing the nature of Da‘wah discourse, and assessing its influence on the socio-political and cultural environment. Adopting a comparative analytical methodology that integrates both historical and contemporary dimensions, the study aims to highlight elements of continuity and change within the Da‘wah experience. It further explores the factors that contributed to the success of Da‘wah in earlier times, as well as the challenges that hinder its effectiveness today, including globalization, secularization, the rise of digital media, and the spread of ideas conflicting with Islamic values. The significance of this research lies in its holistic reading of the Bangladeshi Da‘wah experience, by bridging the rich historical legacy with the evolving contemporary context. Such an approach provides a foundation for envisioning a future-oriented Da‘wah practice that is more impactful and sustainable. The study concludes that the continued success of Islamic Da‘wah in Bangladesh depends on its ability to balance authentic adherence to Islamic principles with innovation in methods and programs, thereby reconciling Islamic identity with the practical needs of society. It also recommends the development of Da‘wah curricula in light of technological changes, strengthening the role of official and community-based Islamic institutions in promoting values of moderation and balance, and investing in the training of Du‘āt capable of addressing modern challenges through scholarly and culturally resonant discourse.